American Hardcore Punk: A Fragmented Movement - Harrison, Brett (My University, 2013)
This paper covers the topic of American hardcore punk music and culture from its beginning in 1980 to 1986 when many bands moved away from hardcore, which was increasingly focused on style rather than ideology. This paper argues that this movement away from hardcore is a result of the fractured nature of hardcore as well as external influences on hardcore. Sources used include primary sources in the form of song lyrics and oral histories as well as a number of secondary sources.
Keywords: Punk culture--United States--History; Punk rock music--History; Hardcore (Music)--History